'We've been thinking you were stupid all this time:' racial microinsults and microinvalidations in a rural Southern high school. Issue 2 (4th March 2021) - Riel, Virginia
ABSTRACT: Racial microaggressions in school have gained increasing attention in recent years. However, scholars often neglect students' experiences of racial microaggressions in rural schools. To fill this gap, this study employs in-depth interviews with 26 students to examine two forms of racial microaggressions – microinsults and microinvalidations. While racial microinsults are slights to students' belonging, ability, and innocence, microinvalidations negate racially marginalized students' experiences through meritocratic and colorblind ideology, or treatment as an outsider. This study finds that black and mixed-race students interpreted racial microinsults using microinvalidations, minimizing the salience of race and asserting meritocratic ideology. White students both elucidated the prevalence of racial microinsults and espoused them during the interviews. These findings underscore the impact of incorporating white and multiracial students' perceptions of racial microaggressions in school, and they suggest the power of meritocracy and colorblindness to mask mistreatment of black and mixed-race students.